MULTI PHASE FLOW MEASUREMENTS WITH THE APPLICATION OF ECT/ERT DECART MULTIMODALITY TOMOGRAPH - Nowakowski, Jacek; Banasiak, Robert; Wajman, Radosław; Sankowski, Dominik (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The multi-phase flow measurements are very important tasks in many areas of industrial processes applications. One of them is undersea exploration of oil in the petroleum industry. The submitted paper presents application of DECART tomograph designed and built in Lodz University of Technology - together with combined measurements of signals acquired from gamma ray measurement system. Use of all measuring modalities allowed for performing measurements of a flow composed of sea water, oil and gas. The paper presents theoretical principles applied to design multimodality tomograph and results of experiments performed in the University of Bergen. Measurement confirmed that multi-modality approach allows giving fast and reliable on-line results of measurements of composition of multi-phase flow. Applied algorithms allowed to speed up on-line measurements and presenting results in a form required in industrial applications. The derived conclusions can be used as guidelines for preparation of industrial applicable construction of tomograph.